Stress determination in cold extrusion by means of visioplasticity method - Plančak, Miroslav (Journal of Production Engineering, 1986)
The knowledge of stress-strain state in the work-piece during deformation process is very significant not only for the determination of the basic parameters of the process, but also for optimal design of all the elements of the working system, as well as for maximum use of material workability. Complete stress state within the volume of workpiece in backward extrusion of stelZ was determined on the basis of visioplasticity method: effective stress and stress components. As a boundary condition the radial stress on the container wall. was used. This radial stress was determined by experiment (pin load cell).